2001
DOI: 10.1073/pnas.131198998
|View full text |Cite
|
Sign up to set email alerts
|

Timing of metamorphosis and the onset of the negative feedback loop between the thyroid gland and the pituitary is controlled by type II iodothyronine deiodinase in Xenopus laevis

Abstract: Two important features of amphibian metamorphosis are the sequential response of tissues to different concentrations of thyroid hormone (TH) and the development of the negative feedback loop between the pituitary and the thyroid gland that regulates TH synthesis by the thyroid gland. At the climax of metamorphosis in Xenopus laevis (when the TH level is highest), the ratio of the circulating precursor thyroxine (T 4) to the active form 3,5,3-triiodothyronine (T3) in the blood is many times higher than it is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 43 publications
6
44
0
1
Order By: Relevance
“…Previous work has shown that this transcript is TH responsive in tail and that overexpression of this enzyme inhibits metamorphosis (Huang et al, 1999). In concordance with previous observations, we did not see an increase in iodothyronine 5Ј-deiodinase II transcript that encodes an "activating" enzyme that converts T 4 to the more bioactive T 3 (data not shown; Huang et al, 2001). Glycoproteins (genes 18 and 19) that are also transiently up-regulated at NF stage 58 have been shown to be expressed in the outer epidermal layer of the tadpole and may play a role in the integrity and function of the larval skin (Furlow et al, 1997).…”
Section: Discussionsupporting
confidence: 93%
“…Previous work has shown that this transcript is TH responsive in tail and that overexpression of this enzyme inhibits metamorphosis (Huang et al, 1999). In concordance with previous observations, we did not see an increase in iodothyronine 5Ј-deiodinase II transcript that encodes an "activating" enzyme that converts T 4 to the more bioactive T 3 (data not shown; Huang et al, 2001). Glycoproteins (genes 18 and 19) that are also transiently up-regulated at NF stage 58 have been shown to be expressed in the outer epidermal layer of the tadpole and may play a role in the integrity and function of the larval skin (Furlow et al, 1997).…”
Section: Discussionsupporting
confidence: 93%
“…tissue morphogenesis (Becker et al 1997, Kawahara et al 1999, Huang et al 2001; the presence of DII mRNA at stage 62 of development but not at stage 56 (Huang et al 2001); the observation that TSH mRNA expression levels increase during metamorphosis, peak at climax and then decline rapidly (Buckbinder & Brown 1993); and the claim that T 4 does not downregulate TSH expression (Huang et al 2001). However, as discussed earlier, our study along with several earlier studies clearly show that negative feedback is active early in prometamorphosis.…”
Section: Discussionsupporting
confidence: 74%
“…More recently, it was shown that treatment of early prometamorphic X. laevis tadpoles with the goitrogen, methimazole, elevated pituitary TSH mRNA levels (Buckbinder & Brown 1993, Huang et al 2001. Taken together, the accumulated data lead to the rejection of the hypothesis that negative feedback is turned on specifically at metamorphic climax (see Huang et al 2001). Huang and colleagues (2001) recently addressed the issue of thyroidal regulation of the pituitary gland during amphibian metamorphosis and the establishment of negative feedback.…”
Section: Discussionmentioning
confidence: 99%
“…However, our result showed muscle cell death at stage 57 when T3 is detectable at first (0.89 nM; Leloup and Buscaglia, 1977). Although the thyroxine concentration is 3.7 nM at this stage, T3 could not be generated from thyroxine in tail, because the tail has almost no mRNA of type II iodothyronine deiodinase (St. Germain et al, 1994;Huang et al, 2001). Therefore, tail muscle cells dying at this stage should be very sensitive to T3.…”
Section: Tail Muscle Cells Start Pcd At Stage 57 In Response To Thmentioning
confidence: 97%
“…6A,B). A decrease of the fluorescence was observed without any morphologic changes of the remaining cells after stage 57 when the endogenous T3 becomes scarcely detectable in plasma (Leloup and Buscaglia, 1977) and type II iodothyronine deiodinase (activating enzyme of thyroxine) is not expressed in tail (Huang et al, 2001). Some GFPpositive cells disappeared between early and late stage 57.…”
Section: Dntr Overexpression Inhibits Muscle Cell Death Before the Tamentioning
confidence: 98%